Prospective cohort study of electrodiagnostic abnormality characterization in pronator quadratus associated with end-to-side nerve transfers for ulnar neuropathy at the elbow. Issue 1 (1st January 2023) - Rathagirishnan, Raahulan; Ritsma, Benjamin; Trier, Jessica; Daneshvar, Parham; Hendry, Michael
Abstract: Ulnar neuropathy at the elbow (UNE) is a common compressive neuropathy that affects the median nerve. Conservative management for mild-to-moderate UNE is an important first step, but generally, develops a plateau in benefit. A specific technique, referred to as a supercharged 'end-to-side' (SETS) nerve transfer can successfully restore pinch, fine motor dexterity and grip strength. A pre-surgical workup flow for UNE patients has been developed, which includes electrodiagnostic (EDX) studies completed to assess the recipient ulnar nerve and the donor median nerve to pronator quadratus (PQ). There is little evidence that the assessment of the PQ muscle is necessary in a non-traumatic setting. A prospective cohort study of patients who present with clinical and/or EDX evidence of ulnar compressive neuropathy, with clinical evidence of motor dysfunction, was assessed for health PQ donor in routine pre-operative workup. We aim to provide justification that SETS for UNE should not be delayed to acquire PQ EDX studies.